Applications of Diquafosol Sodium in Ophthalmology: A Comprehensive Review of Therapeutic Utility - Chelsea Qiu Lin Tan; Duoduo Wu; Xin Yun Toh; Blanche Xiaohong Lim; Kendrick Co Shih; Louis Tong; Chris Hong Long Lim (Life)
Diquafosol sodium is a purinergic P2Y2 receptor agonist that is garnering much interest for its potential therapeutic benefits in ocular surface management. This review provides a comprehensive analysis of diquafosol’s pharmacology, clinical effectiveness, and role in the evolving landscape of ocular surface management. Future research should focus on optimising formulations, treatment duration, and exploring potential combination therapies to maximise therapeutic outcomes. By targeting underlying pathophysiological mechanisms, diquafosol represents a significant advancement in ocular surface management and a valuable addition to existing therapies.